2013
DOI: 10.1016/j.jmb.2013.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of MAVS Regulation at the Mitochondrial Membrane

Abstract: Mitochondria have emerged as critical platforms for antiviral innate immune signaling. This is due in large part to the mitochondrial localization of the innate immune signaling adaptor MAVS (mitochondrial antiviral signaling protein), which coordinates signals received from two independent cytosolic pathogen recognition receptors (PRRs) to induce antiviral genes. The existence of a shared adaptor for two central PRRs presents an ideal target by which the host cell can prevent cellular damage induced by uncont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
136
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(140 citation statements)
references
References 97 publications
1
136
1
2
Order By: Relevance
“…4C). Next, we analyzed the protein expression of MAVS, which functions as an adaptor protein for RLR-mediated signaling pathways (15). It is reported that proteasome-mediated MAVS degradation occurs after RLR activation, and this degradation is required for downstream signaling leading to type I IFN production (16).…”
Section: Radiosensitizing Effects Of the Rlr Agonist On Nsclc Cellsmentioning
confidence: 99%
“…4C). Next, we analyzed the protein expression of MAVS, which functions as an adaptor protein for RLR-mediated signaling pathways (15). It is reported that proteasome-mediated MAVS degradation occurs after RLR activation, and this degradation is required for downstream signaling leading to type I IFN production (16).…”
Section: Radiosensitizing Effects Of the Rlr Agonist On Nsclc Cellsmentioning
confidence: 99%
“…However, both are initially characterized as dsRNA-binding proteins that respond to poly (I:C), a synthetic form of dsRNA and actually, they prefer to different-sized poly (I:C) [7,8]. Following recognition of such ligands, RIG-I and MDA5 are activated and interact with a mitochondrial antiviral signaling protein (MAVS, also known as IPS-1/ VISA/Cardif), to transit antiviral signaling to downstream signaling molecules (such as TBK1 and IRF3/7) and finally orchestrate the IFN antiviral response [2,3,9].…”
Section: Introductionmentioning
confidence: 99%
“…In C. idella, CiLGP2 has been proved to inhibit CiMDA5 transcripts and suppress the CiIPS-1-mediated signaling pathway defense against poly I:C (Chen et al, 2015b). And as known, LGP2 has higher RNA-binding affinity compared to MDA5 (Bruns and Horvath, 2014), and LGP2 has been demonstrated to interact with IPS-1 that interferes with IPS-1 dimerization and prevents its vital association with the downstream signaling molecule TRAF3 (Jacobs and Coyne, 2013). LPS and PGN as the major cell wall components of gram-negative and gram-positive bacteria are capable of stimulating the innate immune system.…”
Section: Discussionmentioning
confidence: 99%